Community Empowerment through Eco-Crowdinvesting in Green Business for Sustainable and Eco-Friendly MSMEs - Kurnianingsih; Prasetyo, Totok; Hendrawati, Dwiana; Lathief, Muttabik Fathul; Saddewisasi, Wyati; Sahid (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
The COVID-19 pandemic, coupled with climate change repercussions, has gravely impacted global economies, notably the MSMEs in Kelurahan Meteseh. These MSMEs, which play key roles in local tourism and cuisine, struggle with energy and capital issues. This community service program addresses these challenges by implementing a green economic ecosystem for these SMEs, leveraging digital platforms, and promoting environmentally friendly business operations. Methodologically, the project encompassed preparation, technology deployment and installation, technology transfer, and mentoring. To address these issues, a community service program introduced Eco-Crowdinvesting green business technology with solar panels to help MSMEs recover sustainably. Solar panels and the Eco-Crowdinvesting platform reduce operational costs, improve finance, and strengthen MSMEs, making energy affordable for them. In line with national digital and green economy strategies, this program gives MSMEs access to solar power and an innovative financing platform, strengthening their economic resilience, promoting sustainable business practices, and increasing environmental awareness.